The Eksperimentation Study of Wave Transmission Trough Type Of Hollow Cube Breakwater - Daniel Daniel; Budiman Budiman (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Erosion that occurs in break water by wave sand currents is a serious problem along coastal and inland shore [1]. This study aimed to assess the effect of the model height (Hm) and the pole density on the model on the reduction of the wave height and on the relationship between the non-dimensional parameter. The research was experimental with 2D physical model simulation which was conducted in the laboratory of Marine Engineering Faculty, Hasanuddin University. Several of configurations of Hollow-type breakwater models were made with different densities and model heights. The model scale use was 1:10 for the three model variations ((M1KB, M2KB, and M3KB) with the variations of the periods and of the wave height, at 0,25 m water depth. The research results indicated that the parameters which showed significant effects were the model height and the model density. These parameters showed the t